Asālīb Ta’līm Al-Lughah Al-‘Arabiyah Li-Ghairi Al-Nāṭiqīn Bihā - Hadjer Mokhtari (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This article topic is about the common strategies of teaching Arabic to non-native speakers, where language teaching began from the ancient era until our time now, due to the old contact of the non-Arabs, their language and their culture with the Arabs, the level of education rose first to preserve the Arab language and heritage from disappearance and distortion. Then the foreigners' interest in him through the ages, this prompted Arab scholars to devote their efforts and develop ways to teach it as a second language to non-native speakers. And that’s because teaching Arabic requires great experience and effort, and complete knowledge, in order to learn and teach it, and this is what will be presented below.يصب موضوع هذا المقال حول مجمل الإستراتيجيات الشائعة لتدريس اللّغة العربية لغير الناطقين بها ، حيث أنّ تدريس اللّغة بدأ منذ العصر القديم حتى عصرنا المعاصر هذا ونظرا للاحتكاك الذي كان قديما من طرف الأعاجم ولغتهم وثقافتهم مع العرب، ارتفع مستوى التعليم أولا للحفاظ على اللغة والموروث العربي من التحريف والزوال والتشويه، ثم بعد ذلك إهتمام الأعاجم به عبر العصور، ما دفع العلماء العرب لتكريس جهودهم فيها ووضع طرق لتدريسها كلّغة تانية لغير ناطقيها، اذ أنّ تدريسها يتطلب خبرة وجهدا كبيرين وإلماما كلّيا باللّغة العربية لأجل التمكن منها و التمكن من تعليمها.